Bela Negara Sebagai Implementasi Nilai Pancasila Bagi Generasi Muda - Putri, Mas Fierna Janvierna Lusie; Rahman, Arip; Rahmawati, Elma; Ningsih, IndahFuji; Hidayat, Wahyu (CV. Kurnia Grup, 2024)
Awareness of state defence means being willing to serve the country and make sacrifices to defend it. In addition, there are several factors that cause students' awareness of state defence to decline, such as the entry of foreign cultures and the rapidly growing role of globalisation. The purpose of this study is to analyse the awareness of students in the millennial generation era in loving the country, awareness of the nation and state, belief in the supremacy of Pancasila, willing to sacrifice to defend the nation and state. This research method uses qualitative assessment with literature review. The author uses data from various sources including books, journals, and online media. The results showed that the awareness of millennial era students about state defence is increasing, because students are the young generation who can change the nation's best progress for the development of the next generation because there are still many students who are not too concerned with state defence. Therefore, it is very important for students in the millennial generation era to be smarter in choosing information and using social media. Students in the millennial generation era are expected to have the ability to change the order of the newly formed state, believe in Pancasila as the state ideology, and apply the values of Pancasila and state defence in everyday life.